2008
DOI: 10.1086/587519
|View full text |Cite
|
Sign up to set email alerts
|

Moxifloxacin Monotherapy Is Effective in Hospitalized Patients with Community‐Acquired Pneumonia: The MOTIV Study—A Randomized Clinical Trial

Abstract: Background. The aim of this study was to show that sequential intravenous and oral moxifloxacin monotherapy (400 mg once per day) is as efficacious and safe as a combination regimen (intravenous ceftriaxone, 2 g once per day, plus sequential intravenous and oral levofloxacin, 500 mg twice per day) in patients hospitalized with community-acquired pneumonia.Methods. We conducted a prospective, multicenter, randomized, double-blind noninferiority trial. Patients with a Pneumonia Severity Index (PSI) of III-V were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 22 publications
1
44
0
6
Order By: Relevance
“…The same dosage and administration schedule developed in Europe and the United States is also employed in Japan, and the drug is expected to be highly useful as outpatient treatment for mild and moderate community-acquired pneumonia. Although the results of many clinical studies have been reported in other countries [1][2][3][4][5], few studies on patients with respiratory infection have been performed in Japan, and to our knowledge, only two domestic clinical studies have been reported [6,7]. Also, detailed evaluation of the pharmacokinetics of MFLX has not been conducted in Japanese patients with community-acquired pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…The same dosage and administration schedule developed in Europe and the United States is also employed in Japan, and the drug is expected to be highly useful as outpatient treatment for mild and moderate community-acquired pneumonia. Although the results of many clinical studies have been reported in other countries [1][2][3][4][5], few studies on patients with respiratory infection have been performed in Japan, and to our knowledge, only two domestic clinical studies have been reported [6,7]. Also, detailed evaluation of the pharmacokinetics of MFLX has not been conducted in Japanese patients with community-acquired pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…After further excluding duplicate publications ( Fig. 1), 16 RCTs fulfilling the inclusion criteria were included [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Two were published only as conference proceedings and contact with the authors could not be established [6,13].…”
Section: Resultsmentioning
confidence: 99%
“…No differences in mortality or an increased eradication rate in the fluoroquinolone arm were found when comparing a fluoroquinolone versus a beta-lactam plus a macrolide [25][26][27]. One clinical trial by Torres et al [24] did not observe differences in mortality after comparing moxifloxacin monotherapy with ceftriaxone plus levofloxacin in a cohort of CAP patients including 10 % with severe pneumonia (PSI score IV or V). Thirteen observational studies were identified.…”
Section: Wardmentioning
confidence: 99%